Attention in vision : perception, communication, and action - van der Heijden, A. H. C. (Psychology Press, 2004)
(from the foreword) Attention in Vision: Perception, Communication, and Action is a research monograph presenting a selective review of empirical findings on visual attention and a new theoretical account of the findings. The present book by Van der Heijden builds on his previous works. The basic assumption that the perceptual categorisation system is unlimited in processing capacity is more or less taken for granted rather than argued anew. SLAM is reviewed, but the focus is on higher-order control processes and overarching theoretical issues. In the terminology used in the book, Van der Heijden attempts to explain how the Intending Mind uses Visual Perception for generating propositions (in report tasks) and moving the body (act tasks) in the physical world. Inspired by Turing's description of a universal machine, the Intending Mind is explicated as a sequence of states in an intentional machine. In report tasks, the Intending Mind goes through successive cycles of selecting an object (filtering) and determining the value of an attribute to be reported (pigeon-holing). In act tasks, the Intending Mind goes through successive cycles of selecting an object and extracting those parameters of the object that are needed for action. Complex behaviour is generated by organising such cycles hierarchically. The overall structure of the book is exceedingly clear and logical.